SOIL COMPACTION OF TIDAL RICE FIELD FROM USE ALSINTAN (CASE STUDY OF TANJUNG LAGO DISTRICT, BANYUASIN REGENCY) - Saputra, Suganda C.; Armanto, M. Eddy; Sodik, Momon (BIOVALENTIA: Biological Research Journal, 2020)
Combine harvester is a rice harvester that can cut the panicles of standing plants, knock down and clean the grain while crossing the rice fields. The use of combine harvester can potentially damage the soil, the soil becomes hard and the use of fuel causes potential air pollution in the rice field environment. The objectives of this study were to identify the impact of soil compaction due to the use of a combine harvester machine and to determine what physical properties affect the soil compaction due to the use of a combine harvester machine. Equipment and materials used for the sand cone test in this study include:transparent bottles, calibration funnels, plates for sand funnels, hammers, spoons, brushes, chisels, scales and sand. The results showed that soil compaction causes porosity and soil permeability was reduced so that it can inhibit plant growth. Soil compaction affects soil physical properties such as bulk density, porosity, and groundwater content.Â